Modelling of large diesel intake and exhaust system acoustics using one dimensional (1D) simulation and experimental verification - Bowden, David Robert (Curtin University, 2017)
This thesis is aimed at simulation of the acoustic and gas flow performance of intake and exhaust system components representative of large marine diesel engines. Modelling and simulation was conducted using 1D CFD in a ‘virtual’ test bench. An experimental acoustic transmission loss test bench (zero flow) was designed and developed to provide validation for the simulation. A finite element analysis of a large marine muffler’s shell was conducted to assess possible interactions.